Simple endovascular thoracic aortic stenting rescues a wrongly deployed frozen elephant trunk during a modified procedure. Issue 2 (February 2021) - Reid, Gregory; Mork, Constantin; Mujagic, Edin; Berdajs, Denis
We report a bail out approach of endovascular thoracic aorta repair following incorrect deployment of a modified frozen elephant trunk stent graft into the false lumen. A 76-year-old patient was admitted to our Emergency Department. A computed tomography angiography scan showed type I DeBakey aortic dissection. An emergency modified frozen elephant trunk procedure was performed. Immediate postoperative computed tomography angiography showed that the distal segment of the stent was deployed in the false lumen, probably through a re-entry tear at the descending thoracic aorta. Emergency endovascular repair of the thoracic aorta, as well as angioplasty of the superior mesenteric artery and left iliac artery, were performed.